Ingeniería inversa y cognición : ¿algunas remembranzas panglossianas? (2014)
ABSTRACT: Daniel C. Dennett has dedicated a great part of his work to the conception of an application of reverse engineering and adaptationism in order to explain the evolution of the human mind. Dennett sees this perspective as a promising possibility in the development of a scientific psychology, in contrast to the “eliminative materialism” of neuroscience. The article provides a conceptual approach and examines a philosophical precedent in the discussions regarding adaptationism in biology and evolutionary psychology: intentionality or the theory of intentional systems.